(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: Clinical guidelines for acute non-specific low back pain recommend avoiding imaging studies, refraining from strong opioids and invasive treatments, and providing information to patients to stay active. Despite these recommendations, many patients undergo diagnostic and therapeutic assessments that are not in line with the current evidence. AIM: To assess the management of acute non-specific low back pain by Swiss general practitioners (GPs) and their adherence to guideline recommendations. METHODS: We performed a survey using two clinical case vignettes of patients with acute non-specific low back pain without red flags or neurological deficits. The main differences between the vignettes were sex, age, profession, pain duration and medical history. GPs were asked about their management of those patients. RESULTS: Of 1253 GPs, 61% reported knowing current clinical guidelines and 76% being aware of “Choosing Wisely” recommendations. Diagnostic evaluations included X-ray (18% for vignette 1, 32% for vignette 2) and magnetic resonance imaging (MRI) (31% and 62%). For pain management, GPs recommended mostly non-steroidal anti-inflammatory drugs, paracetamol and metamizole. Treatments with potential harm included muscle relaxants (78% and 77%), oral steroids (26% and 33%), long-acting opioids (8% and 11%) and spinal injections (28% and 42%). A very high proportion recommended activity restrictions (82% and 71%) and some recommended bed rest (3% and 2%). CONCLUSION: Although GPs reported being aware of current guideline recommendations, management of acute non-specific low back pain was not in line with these recommendations. A substantial proportion of GPs considered imaging, treatments (e.g. muscle relaxants, long-acting strong opioids), and activity and work restrictions with potentially harmful consequences.